Losing the identity of a hockey player: the long-term effects of concussions - Engström, A.; Jumisko, E.; Shahim, P.; Lehto, N.; Blennow, K.; Zetterberg, H.; Tegner, Y. (Concussion, 2020)
Aim:To describe what suffering multiple concussions meant for former semi-professional or professionalhockey players who were forced to end their career. Results: Nine former Swedish hockey players, who once played on national or professional teams were interviewed. The interviews were analyzed with ref-erence to hermeneutic phenomenology to interpret and explain their experiences. The theme of losingone`s identity as a hockey player was constructed from five subthemes: being limited in everyday life, returning to the hockey stadium as soon as possible, forming a post career identity, lacking understanding and support, and preventing injuries by respecting other players. Conclusion: The former hockey players struggled with developing their off-the-ice identities and with finding other sources of meaning for theirlives.Lay abstract:Despite considerable attention to improving the initial management of concussions sufferedby hockey players, few studies have examined their long-term effects. In response, the study reported hereaimed to describe what suffering multiple concussions meant for former semi-professional or professional hockey players who were forced to end their career. Nine former Swedish hockey players, who once played on national or professional teams were interviewed and the interviews were analyzed in order to interpret and explain their experiences. The overall theme was formulated as losing one`s identity as a hockey player.In conclusion, the former hockey players seem to struggle with developing their off-the-ice identities and with finding other sources of meaning for their lives